2022
DOI: 10.1021/acs.inorgchem.1c03675
|View full text |Cite
|
Sign up to set email alerts
|

Telluride Nanocrystals with Adjustable Amorphous Shell Thickness and Core–Shell Structure Modulation by Aqueous Cation Exchange

Abstract: Engineering the structure of core−shell colloidal semiconductor nanoparticles (CSNPs) is attractive due to the potential to enhance photo-induced charge transfer and induce favorable optical and electronic properties. Nonetheless, the sensitivity of telluride CSNPs to high temperatures makes it challenging to precisely modulate their surface crystallinity. Herein, we have developed an efficient strategy for synthesizing telluride CSNPs with thin amorphous shells using aqueous cation exchange (ACE). By changing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The CEf nonepitaxial strategy has shown a wide applicability for construction of various chalcogenide semiconductor shells on plasmonic metal cores featuring well‐defined interfacial properties. [ 87–94,141–154 ] This was established on judicious modulation of the chemical thermodynamics and kinetics of cation exchange reactions which can be simply described by Equation ( ) .MnormalmX+nNm+9extrue→solvent or ligand NnormalnX+mMn+where M and N refer to the host cations and guest cations, respectively, and X stands for the anions. Of particular importance, herein, the hard and soft acids and bases (HSAB) theory is a fundamental rule dominating the driving force for cation exchange, primarily by regulation of the interaction strength between cations and the ligand or solvent molecules.…”
Section: Cef Nonepitaxial Growth Of Plasmonic Metal@semiconductor Pho...mentioning
confidence: 99%
See 1 more Smart Citation
“…The CEf nonepitaxial strategy has shown a wide applicability for construction of various chalcogenide semiconductor shells on plasmonic metal cores featuring well‐defined interfacial properties. [ 87–94,141–154 ] This was established on judicious modulation of the chemical thermodynamics and kinetics of cation exchange reactions which can be simply described by Equation ( ) .MnormalmX+nNm+9extrue→solvent or ligand NnormalnX+mMn+where M and N refer to the host cations and guest cations, respectively, and X stands for the anions. Of particular importance, herein, the hard and soft acids and bases (HSAB) theory is a fundamental rule dominating the driving force for cation exchange, primarily by regulation of the interaction strength between cations and the ligand or solvent molecules.…”
Section: Cef Nonepitaxial Growth Of Plasmonic Metal@semiconductor Pho...mentioning
confidence: 99%
“…The CEf nonepitaxial strategy has shown a wide applicability for construction of various chalcogenide semiconductor shells on plasmonic metal cores featuring well-defined interfacial properties. [87][88][89][90][91][92][93][94][141][142][143][144][145][146][147][148][149][150][151][152][153][154] This was established on judicious modulation of the chemical thermodynamics and kinetics of cation exchange reactions which can be simply described by Equation ( 4).…”
Section: Synthesis and Modulationmentioning
confidence: 99%
“…According to the theory of hard and soft acids and bases, TPP is a soft base that has different coordination abilities with metal ions. In this reaction, metal nitrate aqueous solution and TPP, which was dissolved by a trace amount of toluene, were introduced into Au@Ag 2 X NCs aqueous colloid and stirred for a while to form a uniform mixture with a solid-solution-liquid interface (TPP-aqueous-toluene), and then through hydrothermal treatment, the TPP would coordinate with soft acid Ag + in the amorphous Ag 2 X shell preferentially, which induced the CER between the metal cation in solution and Ag + in the shell, forming a single-crystalline semiconductor shell with low defect heterointerfaces, ,, successfully achieving topological conversion of aqueous cations and obtaining NMS C–S NCs with various compositions. The core–shell structure was not changed or be damaged significantly after CER, which was due to the topotactic nature of CER transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The CER has been widely used to construct NCs with tunable structures and morphologies since the 1990s, among which the nonepitaxial growth method induced by CER is considered an essential strategy for precisely regulating the synthesis of C–S NCs with ideal properties due to its various adjustable parameters like surface ligands, solvents, and kinds of cations. Although nonepitaxial growth induced by CER has been reported to synthesize a variety of NMS C–S NCs, the generality and environmental friendliness of this method are limited because most of the reactions are performed in organic solvents and require initiation with TBP, which is volatile and inflammable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that the synthesis of hetero-nanostructures with large lattice mismatches was also achievable through delicate control of CER, which can also lead to complex hybrid nanostructures. [79][80][81][82][83][84] Therefore, the compromise between the ease of cation exchange and the degree of interfacial strain should be carefully met and be considered prior to the actual synthetic works, which requires the development of theoretical tools that predict the feasibility of cation exchange along certain crystallographic directions.…”
Section: In-depth Understanding Of the Crystallographic Featuresmentioning
confidence: 99%